The Valuation of Hedge Funds’ Equity Positions - Cici, Gjergji; Kempf, Alexander; Puetz, Alexander (Journal of Financial and Quantitative Analysis, 2016)
Abstract We provide evidence on the valuation of equity positions by hedge funds. Reported valuations deviate from standard valuations based on closing prices from the Center for Research in Security Prices for roughly 7% of the positions. These equity valuation deviations are positively related to illiquidity and price volatility of the underlying stocks. They respond to past performance and intensify after an advisor starts reporting to a commercial database. Furthermore, advisors with more valuation deviations show a stronger discontinuity in their reported returns around 0, manage a higher fraction of potentially fraudulent funds, report smoother returns, and exhibit an upward spike in their December reported returns.